(untitled) (MAUSAM, 1989)
This paper presents essentially a mathematic model to study the mechanism of the change of volume pertaining to the growth of a hailstone. The variations of concentration, with respect to time as well as the growth rate for different sizes of embryo are Investigated, While this study is in accord with the findings of Xu (1983), Ziegler (1983), Nelson (1983) and Heyms1ield (1982), it brings out soil important characteristic features in respect of the variations of Ice concentration and particularly, a drop In the concentration with increase in radius in initial stages.